ANALYSIS OF EARNINGS MANAGEMENT ON PT BERKAH MULIA BETON - Irma Christiana; Fika Jayanti (Journal of International Conference Proceedings (JICP), 2019)
Earnings management is an intervention activity with certain objectives in the external financial reporting process, to obtain several benefits. This study aims to analyze earnings management at PT. Berkah Mulia Beton Deli Serdang by using solvency ratios and profitability ratios for the period 2016-2017. The profit management proxy in this study uses discretionary accruals. While the solvency ratio is measured using debt to total asset ratio (DAR) and debt to equity ratio (DER), and the profitability ratio is measured using return on assets (ROA) and return on equity (ROE). This study uses quantitative data, data collection techniques using documentation techniques and data analysis techniques using descriptive analysis based on time series methods. The results of the study concluded that PT Mulia Beton Deli Serdang practices earnings management with income, decreasing using the big bath strategy with the first in, first out (FIFO) inventory recording method, and the double declining method for depreciating fixed assets office and factory. Where the solvency and profitability of the company motivates management to practice earnings management.